2010
DOI: 10.1068/i0401
|View full text |Cite
|
Sign up to set email alerts
|

The Shading Cue in Context

Abstract: The shading cue is supposed to be a major factor in monocular stereopsis. However, the hypothesis is hardly corroborated by available data. For instance, the conventional stimulus used in perception research, which involves a circular disk with monotonic luminance gradient on a uniform surround, is theoretically ‘explained’ by any quadric surface, including spherical caps or cups (the conventional response categories), cylindrical ruts or ridges, and saddle surfaces. Whereas cylindrical ruts or ridges are repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Studies that used complex illuminated objects with strong lighting direction cues concluded that lighting cues guide shape-from-shading (6, 7), whereas studies that used weaker lighting cues concluded that they have little effect (8)(9)(10)(11)(12). We discuss the lighting cues in previous studies in further detail in SI Discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that used complex illuminated objects with strong lighting direction cues concluded that lighting cues guide shape-from-shading (6, 7), whereas studies that used weaker lighting cues concluded that they have little effect (8)(9)(10)(11)(12). We discuss the lighting cues in previous studies in further detail in SI Discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Koenderink, van Doorn, Christou, and Lappin (1996) and found that adding surfacerelated information such as shading, texture, and motion yielded only small improvements in shape judgments beyond those obtained with boundary contours alone. Wagemans, van Doorn, and Koenderink (2010) found that contour shape strongly influenced perception of shape from shading.…”
Section: Boundary Contoursmentioning
confidence: 99%
“…The important point, however, is that the image information is inherently ambiguous. Moreover, experiments have found significant variability between individuals, within individuals, strong effects of the outer contour shape, and both interactions and inconsistencies among spatially separate surface regions (Kleffner & Ramachandran, 1992;van Doorn et al, 2011;Wagemans, van Doorn, & Koenderink, 2010).…”
Section: Image Shadingmentioning
confidence: 99%
“…It is interesting, for example, that the illusion is stronger for upright than for inverted faces (Hill & Bruce, 1993). Moving away from the special case of faces, Langer and Bülthoff (2001) tried to compare different assumptions about 3-D shape and concluded that the convexity assumption is as strong as two other assumptions: the viewpoint from above and the light from above (but see also van Doorn, Koenderink, & Wagemans, 2011;Wagemans, Van Doorn, & Koenderink, 2010). What is important for this review is that a bias for 3-D convexity over 3-D concavity does not imply an equivalent bias for 2-D convexity over 2-D concavity, because of the difference discussed earlier in how 2-D information is information about 3-D surface curvature-namely, the fact that a concave contour is not the projection of a concave surface.…”
Section: Questionmentioning
confidence: 99%